An effect of the outpatient rehabilitation programme in patients with chronic respiratory diseases - Jakub Zatloukal (Acta Universitatis Palackianae Olomucensis. Gymnica, 2013)
BACKGROUND: Pulmonary rehabilitation is a common type of complex treatment especially in patients with chronic obstructive pulmonary disease (COPD). By contrast, only few rehabilitation centres in the Czech Republic provide pulmonary rehabilitation programme to non-COPD patients. OBJECTIVE: To find out if the rehabilitation programme has a similar effect in patient with obstructive and restrictive ventilatory disorder. METHODS: Twenty-eight patients with either COPD or pulmonary sarcoidosis (PS) have been enrolled for the 6-week rehabilitation programme. Lung functions, maximal inspiratory (MIP) and expiratory (MEP) mouth pressures, chest expansion at the level of the 4th intercostal space (IC) and at the level of the xiphoid process (XP), six-minute walk test, health-related quality of life using the St. George’s Questionnaire (SGRQ) and fatigue occurrence using the Multidimensional Assessment of Fatigue scale (MAF) were tested at the baseline and after 6 weeks. The rehabilitation programme consisted of exercise training, ventilatory muscle training, respiratory physiotherapy and soft-tissue techniques. RESULTS: Patients with COPD improved significantly (p < .05) in MIP by 17% (10.5 cm H2O), MEP by 18% (16.8 cm H2O), IC by 65% (1.7 cm), XP by 90% (1.9 cm), six-minute walk distance (6MWD) by 15% (64.1 m) and SGRQ by –28% (–12.3 points). Patients with PS improved significantly (p < .05) in MIP by 25% (20.1 cm H2O), IC by 29% (1.3 cm), XP by 29% (1.3 cm) and 6MWD by 6% (31.6 m). The change in lung functions and MAF in both groups; MEP and SGRQ in PS group were insignificant after the 6-week rehabilitation programme. CONCLUSIONS: The 6-week rehabilitation programme produces similar responses in functional health status of patients with either obstructive or restrictive ventilatory disorder. However, patients with restrictive ventilatory disorder in particular should be encouraged to continue in the programme to enhance the health-related quality of life, which might not be sufficiently affected after 6 weeks.